Eksistensi Tenun Ikat Dayak Sintang dalam Pelestarian Budaya Lokal - Munawar Thoharudin; Mukhamad Zulianto; Chandra Fauzi; Fithra Ramadian; Dewi Puji Astuti; Abdi Roni Pandiangan (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTDayak ikat weaving is a cultural heritage of the indigenous communities in West Kalimantan, holding significant cultural, social, and economic value for the Dayak people. However, the sustainability of this weaving tradition faces several challenges, including modernization, limited cultural documentation, declining interest among younger generations, and suboptimal digital marketing practices. This community service initiative aimed to document the potential of Dayak ikat weaving in Ensaid Panjang Village, Sintang Regency, while describing weaving practices and exploring opportunities for the development of a local culture-based creative economy. A descriptive qualitative approach was employed through observation, interviews, and documentation. The findings indicated that the weaving tradition remains an integral part of Dayak community life and continues to be passed down across generations. The production process still relies on traditional looms, with some artisans utilizing natural dyes derived from forest plants. Beyond its cultural and symbolic significance, Dayak ikat weaving also contributes to local economic development through the diversification of handicraft products and cultural tourism. Therefore, collaborative efforts involving cultural documentation, strengthened digital promotion, and Intellectual Property Rights (IPR) protection are necessary to support the sustainable preservation of Dayak ikat weaving.Keywords: Dayak ikat weaving, cultural preservation, local wisdom, Sintang ABSTRAK enun ikat Dayak merupakan warisan budaya masyarakat adat di Kalimantan Barat yang memiliki nilai budaya, sosial, dan ekonomi yang penting bagi masyarakat Dayak. Namun, keberlanjutan tradisi menenun menghadapi berbagai tantangan, seperti modernisasi, keterbatasan dokumentasi budaya, rendahnya minat generasi muda, serta belum optimalnya pemasaran digital. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendokumentasikan potensi tenun ikat Dayak di Desa Ensaid Panjang, Kabupaten Sintang, serta menggambarkan aktivitas menenun dan peluang pengembangan ekonomi kreatif berbasis budaya lokal. Metode yang digunakan adalah pendekatan deskriptif kualitatif melalui observasi, wawancara, dan dokumentasi. Hasil kegiatan menunjukkan bahwa tradisi menenun masih menjadi bagian penting dalam kehidupan masyarakat Dayak dan diwariskan secara turun-temurun. Proses produksi tenun masih menggunakan alat tradisional dan sebagian memanfaatkan pewarna alami dari tumbuhan hutan. Selain memiliki nilai budaya dan simbolik, tenun ikat juga berkontribusi terhadap peningkatan ekonomi masyarakat melalui diversifikasi produk kerajinan dan wisata budaya. Oleh karena itu, diperlukan upaya kolaboratif melalui dokumentasi budaya, penguatan promosi digital, dan perlindungan Hak Kekayaan Intelektual (HKI) guna mendukung pelestarian tenun ikat Dayak secara berkelanjutan.Kata Kunci: Tenun Ikat Dayak, Pelestarian Budaya, Kearifan Lokal, Sintang